2000
DOI: 10.1074/jbc.m004913200
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Apolipoprotein B-38.9-producing Mutation Causes Fatty Livers in Mice Due to the Reduced Ability of Apolipoprotein B-38.9 to Transport Triglycerides

Abstract: Nonphysiological truncations of apolipoprotein (apo) B-100 cause familial hypobetalipoproteinemia (FHBL) in humans and mice. An elucidation of the mechanisms underlying the FHBL phenotypes may provide valuable information on the metabolism of apo B-containing lipoproteins and the structure-function relationship of apo B. To generate a faithful mouse model of human FHBL, a subtle mutation was introduced into the mouse apo B gene by targeting embryonic stem cells using homologous recombination followed by remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(138 citation statements)
references
References 50 publications
8
129
1
Order By: Relevance
“…The presence of fatty liver was not commented upon in prior reports in which apoB siRNA was delivered in vivo, but a study in which antisense apoB oligonucleotides were used indicated that apoB knockdown did not cause fatty liver (10,21,22,49). However, fatty livers are observed in transgenic mice possessing a mutant apoB gene associated with familial hypobetalipoproteinemia in humans (48). The possibility that apoB knockdown causes fatty liver should be taken into account if apoB is to be considered a therapeutic target in the treatment of hypercholesterolemia in humans.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The presence of fatty liver was not commented upon in prior reports in which apoB siRNA was delivered in vivo, but a study in which antisense apoB oligonucleotides were used indicated that apoB knockdown did not cause fatty liver (10,21,22,49). However, fatty livers are observed in transgenic mice possessing a mutant apoB gene associated with familial hypobetalipoproteinemia in humans (48). The possibility that apoB knockdown causes fatty liver should be taken into account if apoB is to be considered a therapeutic target in the treatment of hypercholesterolemia in humans.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, transgenic mice expressing a truncated form of apoB found in patients with familial hypobetalipoproteinemia, also display a reduced capacity to transport hepatic triglycerides (48). To assess the effects of apoB knockdown on triglyceride transport, we performed oil red staining of liver sections obtained from mice injected with apoB-1 siRNA polyconjugate.…”
Section: Dose-response and Phenotypic Analyses Of Mice Receiving Apobmentioning
confidence: 99%
“…TG synthesis rates were quantified by using [ 3 H]glycerol in the presence of 300 M oleate in the culture media as previously described (31,32). To measure the rate of glucose output, after a pretreatment period of 18 h with MSDC-0602 or vehicle, the hepatocytes were washed extensively with PBS and then incubated for 3 h in 1 mM Krebs-Ringer-Hepes buffer containing 10 mM lactate and 0.5 M glucagon with or without insulin (0.5 M) and MSDC-0602.…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ/Ϫ mice as described previously (24). For gene expression analyses with isolated hepatocytes, cells were stimulated for 6 h with vehicle or dexamethasone (1 M) and 8-bromo-cyclic AMP (1 mM).…”
Section: ϫ/ϫmentioning
confidence: 99%